ANALISIS FAKTOR YANG MEMPENGARUHI KEPUTUSAN STRUKTURAL MODAL PADA PENGEMBANG PERUMAHAAN DI KABUPATEN GOWA - Mihrani Mihrani (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2018)
One of the important decisions faced by financial managers in relation to company operations is the decision on the Capital Structure. F test in this study obtained the value of F arithmetic of 3.130 with a significance of 0.026. With a significance level of 0.05. The significance number is 0.026 <0.05. On the basis of such comparison, then H0 rejected or means variable asset structure, Growth Opportunity, Firm Size, Profitabiltas and Business Risks have a significant influence simultaneously to the variables decision business developers in Gowa regency. The most dominant variable affecting the business decision of the housing developer is Firm Size this is supported by the housing developer to diversify to minimize the failure of the business